Jaminan UUD 1945 dalam Proses Hukum yang Adil - Latif, Abdul (Mahkamah Konstitusi Republik Indonesia, 2010)
One of the principles of rule of law which guarantees by the constitution is regarding the due process of law. Legal acknowledgment, legal guarantee, legal protection, fair legal assurance and equality before the law cannot be separated from the principle of “presumption of innocence”. Both had becoming the absolute condition and its existences are acknowledged, protected, and guaranteed within the rule of law system in Indonesia. However, in a matter of fact there are numbers of regulations which are in contradiction with the 1945 Constitution. One regulation, which is the main discussion of this note, is the Article 32 (1) letter c Law No. 30/2002 on The Committee of the Eradications of Corruption (UU KPK). The implementation of temporary dismissal of Chief of the KPK by the President of the Republic and the unlawful act of Bibit-Chandra’s restraining are deemed to be an act of unlawful discretion and a violation of due process of law as guaranteed by the 1945 Constitution.Latif, Abdul. 2007. Fungsi Mahkamah Konstitusi dalam Upaya Mewujudkan Negara Hukum Demokrasi, Total Media, Yogyakarta.Kusumohamidjojo, Budiono, 2004. Filsaf Hukum: Problematik Ketertiban yang Adil, Grasindo, Jakarta.Kelsen, Hans, 1982. Reine Rechtslehre (Ajaran Hukum Murni), Wien: FranzDeuticke.Rawls, John, 1971. A Theory of Justice, Harvad. UP.Kompas, 2009. Mahkamah Konstitusi diminta Terbitkan Putusan Sela., Edisi Hari Selasa, 27 Oktober 2009, Jakarta.Suseno, Frans Magnis, 1987. Etika Politik. Gramedia. Jakarta.Majalah Konstitusi, 2009, Putusan Sela Bibit-Chandra Menunda Pemberhentian Pimpinan KPK, Edisi Oktober 2009, Nomor 33. Jakarta.Reksodiputro, Mardjono, Jaminan Konstitusi tentang Proses Hukum yang Adil, dalam Buku 70 Tahun Ismail Suny, Sinar Harapan, Jakarta.Tobias, Marc Weber dan R. David Petersen, Pretrial Procedure, A Survey of Constitutional Rights, Charles C. Thomas Publisher, 1978.